Does Navigation Make Spinal Fusion for Adolescent Idiopathic Scoliosis Safer? Insights From a National Database. Issue 19 (1st October 2021) - Kaur, Japsimran; Koltsov, Jayme C.B.; Kwong, Jeffrey W.; Cheng, Ivan; Vorhies, John S.
Abstract : Study Design: Retrospective Cohort. Objective: To evaluate the effect of computer-assisted navigation (NAV) on rates of complications and reoperations after spinal fusion (SF) for adolescent idiopathic scoliosis (AIS) using a nationally representative claims database. Summary of Background Data: Significant controversy surrounds the reported benefits of NAV in SF for AIS. Previous studies have demonstrated decreased rates of pedicle screw breaches with NAV compared to free-hand methods but no impact on complication rates. Thus, the clinical utility of NAV remains uncertain. Methods: Analyses were performed using the IBM MarketScan databases. Patients aged 10 to 18 undergoing SF for AIS were grouped by use of NAV. Patients with nonidiopathic scoliosis were excluded. Univariate and risk-adjusted multivariate analyses were performed. Primary outcomes were neurological complications, any medical complications, and reoperations. Secondary outcomes included adjusted total reimbursements and length of stay. Results: A total of 12, 046 patients undergoing SF for AIS were identified, and 8640 had 90-day follow-up. NAV was used in 467 patients (5.4%), increasing from 2007 to 2015. After risk adjustment, the odds for any complication within 90 days were lower with NAV (OR = 0.61, P = 0.025), but neurological complications were unrelated to NAV ( P = 0.742). NAV was not associated with reoperation within 90 days ( P = 0.757) or 2 years ( P = 0.095). We observed a 25, 038 increase in adjusted total reimbursements ( P < 0.001) and a 0.32-day decrease in length of stay ( P = 0.022) with use of NAV. Conclusion: In this national sample, NAV was associated with a lower rate of total complications but no change in rates of neurological complications or reoperations. In addition, NAV was associated with a large increase in total payments, despite a modest decrease in hospital stay. Considering the increasing popularity of NAV, this study provides important context regarding the utility of NAV for AIS. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textIn a large cohort study, computer-assisted navigation (NAV) in spinal fusion for adolescent idiopathic scoliosis (AIS) was associated with fewer 90-day complications, but no difference in rates of neurological complications or reoperations despite a 25, 000 increase in payments. These results challenge the purported benefits of NAV in treatment of AIS.